Acoustic two-dimensional scattering from cylinders using the method of source simulation technique - P.H. T. Zannin (Archives of Acoustics)
In this work the Method of Source Simulation Technique was used to calculate the scattering of a plane wave by a circular cylinder with random distribution of the surface impedance. The scattering and radiation from vibrating bodies can be expressed by a source system that is located within the envelope of the scatterer or radiator. The Method of Comparative Sources, as is shown in this work, provides an appropriate prediction of the sources strength and consequently of the sound field. The efficiency of the method was verified through the comparison between numerical results and experimental data. The calculation of the scattering was performed for the variants of the method: the single-layer method and the one-point multipole method.